2001
DOI: 10.1001/archpedi.155.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Factors Preventing Gun Acquisition and Carrying Among Incarcerated Adolescent Males

Abstract: Context: Despite the wide availability of guns in the United States, not all delinquent adolescents own guns and not all adolescent gun owners carry them at all times. Research about the factors that prevent high-risk youth from acquiring and carrying guns is limited.Objective: To determine, from the perspective of incarcerated adolescent males, factors that prevent acquiring or carrying guns, either on a temporary or permanent basis. Design and Setting:In-depth, semistructured interviews were conducted with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Some youths reported that they would only buy or borrow a gun from a small circle of trusted friends and family members. 12 As more law enforcement agencies begin to question youths arrested on gun charges about where they obtained their guns, 11 this research serves as a potential reality check. If our data are reasonably generalizable, police should be suspicious of claims that a youth acquired a gun from a total stranger.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some youths reported that they would only buy or borrow a gun from a small circle of trusted friends and family members. 12 As more law enforcement agencies begin to question youths arrested on gun charges about where they obtained their guns, 11 this research serves as a potential reality check. If our data are reasonably generalizable, police should be suspicious of claims that a youth acquired a gun from a total stranger.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reason respondents offered for their preference for new guns was to avoid the risk of having a gun that could be linked to other crimes. 12 New guns were also perceived to be less likely to jam than used guns, a factor that was very important to some youths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Youth report that their awareness of these police practices curtail their gun carrying (Freed, Webster, Longwell, Carrese, & Wilson, 2001). Targeted initiatives with relatively…”
Section: Reduce Youth Access To Gunsmentioning
confidence: 99%